Intrusive memories and ruminations related to violent crime among young offenders: phenomenological characteristics. - Evans, C; Ehlers, A; Mezey, G; Clark, D (2007)
Very little is known about the nature of perpetrator's memories of violent crime. The authors conducted semistructured interviews with a representative sample of 105 young offenders convicted of serious violence, assessing intrusive memories, ruminations, and symptoms of posttraumatic stress disorder related to their violent crime. Forty-eight (46%) participants described significant intrusive memories of the assault, and 38 (36%) reported ruminations related to the assault. Ethnic origin and historical variables explained 19% of the variance of posttraumatic stress disorder symptom severity; intrusion and rumination characteristics added an additional 48% explained variance. The intrusive memories tended to concern the moment when the event turned for the worse for the perpetrator. The findings have implications for risk assessment and therapeutic interventions for violent offenders.